Estudo do desempenho térmico e avaliação das condições de conforto em edifícios antigos: casos de estudo do município de Ovar - Fernandes, J. E. P. (2017)
The latest transposition into Portuguese legislation of the European Directive on the energy performance of buildings (EPBD) has considerably increased the requirements for both new buildings and rehabilitation. In old buildings, architectural and existing materials features condition the available solutions. The most effective energetic refurbishment solution often involves identifying and combining strategies that lead to a cost-optimal solution. To identify the best options within the possible lines of action (at the scale of the envelope, passive strategies, equipment, renewable energy systems), in order to optimize the intervention and improve thermal performance and comfort conditions, it is necessary to perceive the real performance of this type of buildings. Therefore, this paper presents the preliminary results of the study on thermal performance and comfort of a set of case studies located in Ovar. Monitoring included the measurement of hygrothermal parameters and surveys on occupants? thermal sensation.